Routledge International Handbook of Ignorance Studies. - Gross, Matthias. (Routledge International Handbooks Series, 2022)
Once treated as the absence of knowledge, ignorance has now become a highly influential and rapidly growing topic in its own right. This new edition of the seminal text in the field is fully revised and includes new and expanded chapters on a wide range of topics.